2023
DOI: 10.1002/wps.21110
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity between major depressive disorder and physical diseases: a comprehensive review of epidemiology, mechanisms and management

Michael Berk,
Ole Köhler‐Forsberg,
Megan Turner
et al.

Abstract: Populations with common physical diseases – such as cardiovascular diseases, cancer and neurodegenerative disorders – experience substantially higher rates of major depressive disorder (MDD) than the general population. On the other hand, people living with MDD have a greater risk for many physical diseases. This high level of comorbidity is associated with worse outcomes, reduced adherence to treatment, increased mortality, and greater health care utilization and costs. Comorbidity can also result in a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 373 publications
0
9
0
Order By: Relevance
“…Several risk factors have been identified for PPD, including previous depression, postnatal stress, and inadequate support during the postpartum period [8][9][10]. However, recent studies have suggested that other factors, including subclinical inflammation, may also play a key role in the pathogenesis of major depression and of PPD [11][12][13]. The number of studies investigating the potential association between inflammation and the onset of PPD is limited [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors have been identified for PPD, including previous depression, postnatal stress, and inadequate support during the postpartum period [8][9][10]. However, recent studies have suggested that other factors, including subclinical inflammation, may also play a key role in the pathogenesis of major depression and of PPD [11][12][13]. The number of studies investigating the potential association between inflammation and the onset of PPD is limited [14].…”
Section: Introductionmentioning
confidence: 99%
“…Manifested by increased mortality 1 and somatic comorbidity, 2,3 unhealthy lifestyle behavior such as unhealthy diet, alcohol abuse, inactivity and smoking, is common in people with psychiatric diseases. Therefore, a wide range of nutrition guidance, physical activity and smoking interventions emerge globally in psychiatric settings.…”
Section: Introductionmentioning
confidence: 99%
“…This high level of comorbidity is associated with worse outcomes, reduced treatment compliance, increased mortality rates, higher healthcare utilization, and costs. Comorbidities can also lead to a range of clinical challenges, including more complex treatment regimens, issues related to adaptive health behaviors, drug interactions, and adverse events caused by medications used for both physical and mental disorders ( Berk et al, 2023 ). There are numerous risk factors associated with the onset of depression, including stress, pain, physical illnesses, and cognitive decline.…”
Section: Introductionmentioning
confidence: 99%